2018
DOI: 10.1089/g4h.2017.0139
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bingocize®: A Game-Centered Mobile Application to Improve Physical and Cognitive Performance in Older Adults

Abstract: Our findings suggest that the fun and interactive nature of Bingocize engenders high levels of adherence to a health-promoting program in a difficult to serve population, serving as a conduit to potentially improve multiple aspects of quality of life for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…In this investigation, the main focus of the health topics (osteoarthritis and falls prevention) in both conditions was not increasing physical activity. Yet, even more surprising was the fact both groups improved chair stand performance (a test of lower body strength) at the end of the intervention (Shake et al, 2018). We speculate because Bingocize ® is game-centered and interactive, the older adults were motivated to increase their physical activity levels outside of the intervention.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In this investigation, the main focus of the health topics (osteoarthritis and falls prevention) in both conditions was not increasing physical activity. Yet, even more surprising was the fact both groups improved chair stand performance (a test of lower body strength) at the end of the intervention (Shake et al, 2018). We speculate because Bingocize ® is game-centered and interactive, the older adults were motivated to increase their physical activity levels outside of the intervention.…”
Section: Discussionmentioning
confidence: 87%
“…The PAM-10 includes 10 items which are scored (0-100 scale) and then used to categorize an individual on a continuum ranging from level 1 (lowest) to level 4 (highest) in terms of health activation. Additional physical and cognitive performance tests were also administered; details about those tests can be found in Shake et al [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was insufficient information in the sources of parameter estimates to suggest differences in intervention impacts by age, sex, or ethnicity. Previous research has shown [35] and different ethnic groups [36]. However, if certain population groups are more or less likely to respond to the intervention, then this would influence the overall effectiveness and cost-effectiveness.…”
Section: Strengths and Limitationsmentioning
confidence: 98%